Ultrasound as a first-line imaging tool in paediatric appendicitis: diagnostic yield and limitations - Hossain, Mohammad Mahbub; Monowara, Mahmuda (International Journal of Contemporary Pediatrics, 2026)
Background: Acute appendicitis remains a common and clinically significant cause of abdominal pain in children and despite widespread use of ultrasound as the preferred first-line imaging modality, its diagnostic performance continues to show variability across different clinical settings due to factors such as operator dependence and appendix visualization rates. The purpose of the study is to evaluate the diagnostic yield and limitations of ultrasound as a first-line imaging modality in children with suspected acute appendicitis. Methods: This prospective observational study at the Department of Radiology and Imaging, Bangladesh Shishu hospital and institute, Bangladesh (June 2023–July 2024) included 100 pediatric patients with suspected appendicitis. All underwent abdominal ultrasound and final diagnosis was confirmed by surgery, histopathology or clinical follow-up. Diagnostic performance was calculated using 2×2 tables and analyzed with SPSS 25.0. Results: The study included 100 pediatric patients (mean age 10.27±3.33 years), with 58% males. The appendix was visualized on ultrasound in 78% of cases; 55% showed features suggestive of appendicitis and 23% appeared normal. Acute appendicitis was confirmed in 60% of patients. Ultrasound yielded 52 true positives, 35 true negatives, 8 false negatives and 5 false positives, resulting in a sensitivity of 86.7%, specificity of 87.5%, positive predictive value of 91.2%, negative predictive value of 81.4% and an overall diagnostic accuracy of 87.0%. Conclusions: Ultrasound is a reliable first-line imaging tool for pediatric appendicitis, effectively identifying most cases while minimizing the need for invasive or radiation-based investigations.